Gender Responsive Budgeting and Equitable Development in Karawang Regency - Hidayati, Arina; Azzakhusna , Famita (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the implementation of Gender-Responsive Budgeting (GRB), the relationship between economic growth and gender development, and the condition of gender equality within the industrial sector in Karawang Regency. The study employs a descriptive qualitative approach using literature review methods and secondary data analysis derived from regional government documents, Statistics Indonesia (BPS), the Regional Medium-Term Development Plan (RPJMD), and previous scholarly studies. The research focuses on the analysis of public expenditure realization, regional economic growth, gender development, and women’s employment opportunities within Karawang’s industrial areas. The findings indicate that Karawang has experienced relatively strong economic growth driven by industrialization and increasing regional investment. Regional budget realization also demonstrates high levels of efficiency and effectiveness, including a significant increase in the Gender-Responsive Budgeting (GRB) ratio. Furthermore, the improvement in the Gender Development Index (GDI) reflects progress in gender development, particularly in the areas of education, health, and women’s quality of life. However, the study also reveals that the benefits of economic growth have not yet been distributed inclusively. Gender disparities remain evident in labor force participation, wage levels, educational access, and male dominance in strategic positions within the industrial sector. Therefore, stronger gender mainstreaming policies are required through optimizing GRB implementation, strengthening the protection of women workers, expanding access to education and vocational training, and improving development policy monitoring to ensure that economic growth is accompanied by equitable and sustainable development.